2019
DOI: 10.35631/ijmtss.29003
|View full text |Cite
|
Sign up to set email alerts
|

Male and Female Social Media Influencers: The Impact of Gender on Emerging Adults

Abstract: Social media influencers are people who have established a reputation for themselves on social media. Nowadays, a social media influencer has played the important role of a marketing tool for organizations. Organizations use the power of social media influencers to influence and persuade consumers through social media. It is because social media influencers have a huge number of followers in their social media, thus, social media influencers could promote and reach a large number of consumers in a short time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 3 publications
1
14
0
1
Order By: Relevance
“…Previous endorsement literature has concentrated on either the endorser’s characteristics or product attributes and ignored the role of consumer characteristics (Reed, 2002; Tzoumaka et al , 2016). Similarly, earlier work in SMI marketing mainly paid attention to test the gender of influencers (Lokithasan et al , 2019). There is scant attention paid to the biological gender of social media followers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous endorsement literature has concentrated on either the endorser’s characteristics or product attributes and ignored the role of consumer characteristics (Reed, 2002; Tzoumaka et al , 2016). Similarly, earlier work in SMI marketing mainly paid attention to test the gender of influencers (Lokithasan et al , 2019). There is scant attention paid to the biological gender of social media followers.…”
Section: Discussionmentioning
confidence: 99%
“…Some courses require endurance, considering physical strength, and physical work tends to embrace men because they are better at technical work [12]. Males tend to be perceived and wider social networks in terms of position, so they tend to get a higher position in an organization [13]. Besides, men are said to be able to decide without contemplating personal affairs and feelings alone [14].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Lokithasan et al (2019) said that there are differences between male and female influencers' way of influencing people in their lives. Their study showed that female influencers that promote beauty products tend to attract female followers whilst male are more into male influencers that promote games and technology.…”
Section: Social Media Influencers (Smis)mentioning
confidence: 99%
“…Each user on the platform has their own interest and there are variety of social media influencers (SMIs) on the internet. Social media influencers are groups of people that have constructed a reputation for themselves through applying social media platforms to promote oneself (Lokithasan et al, 2019). There are beauty influencers, fashion influencers, food influencers, fitness influencers and etc.…”
Section: Introductionmentioning
confidence: 99%